PENGARUH LINGKUNGAN SEKOLAH, TINGKAT PENDAPATAN ORANG TUA DAN SELF EFFICACY TERHADAP MINAT MELANJUTKAN STUDI DI PERGURUAN TINGGI - Azmi, Nurul; Dhiah Fitrayati (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to determine the influence of the school environment and parents' income level on the interest in continuing studies at university. Using SEM-PLS analysis on SmartPLS 4 software. The results of the study indicate that: (1) the school environment has a positive and significant effect on the interest in continuing studies at university; (2) parents' income level has a negative but significant effect on the interest in continuing studies; (3) self-efficacy has a positive and significant effect on the interest in continuing studies; (4) the school environment has a positive effect on self-efficacy; (5) parents' income level does not have a significant effect on self-efficacy; (6) self-efficacy is able to mediate between the school environment and interest in continuing studies; (7) self-efficacy is not able to mediate between parents' income level and interest in continuing studies.